NUTRITION LEVEL AND PHYSICAL QUALITY OF BALI BEEF ACCORDING TO THE SEX AND AGE OF CATTLE - Agustina, Kadek Karang; Cahya, I Made Ricky Dwi; Widyantara, Gusti Made; Swacita, Ida Bagus Ngurah; Dharmayudha, Anak Agung Gde Oka; Rudyanto, Mas Djoko (Buletin Veteriner Udayana; Vol. 9 No. 2 Agustus 2017, 2017)
This research aims were to measure nutrition level and the physical quality of bali beef according to the age and sex of cattle. A total of 60 bali beef samples have been examined, consisting of 30 male and 30 female, in which they were divided into six age groups. The parameters of quality and nutritions of bali beef included: meat color, pH, water holding capacity, water content, crude protein, fat and ash content. The result showed that according to the sex and age of cattle, the beef quality and nutrition were not significantly different. This indicates that the bali beef have the similar qualities based on the different of sex and age.